2003
DOI: 10.1016/s0009-2509(03)00221-5
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of enzymatic conversion of glucose to lactic acid by reactive extraction

Abstract: Lactic acid is an important commercial product and extracting this out of aqueous solution is a growing requirement in fermentation-based industries and recovery from waste streams. The design of an amine extraction process requires (i) equilibrium and (ii) kinetic data for the acid-amine (solvent) system used. Equilibria and kinetics for lactic acid extraction by Alamine 336 in octanol as a diluent have been determined and compared with other diluents studied earlier. An approach for extracting the lactic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 20 publications
2
65
0
Order By: Relevance
“…The complexation of lactic acid with Alamine 336 in octanol at 30 • C is described as follows (Wasewar et al, 2003):…”
Section: Equilibriamentioning
confidence: 99%
“…The complexation of lactic acid with Alamine 336 in octanol at 30 • C is described as follows (Wasewar et al, 2003):…”
Section: Equilibriamentioning
confidence: 99%
“…• C is described as follows (Wasewar et al, 2003): The equilibria in the aqueous phase are described as follows (Poole and King, 1991): …”
Section: Equilibriamentioning
confidence: 99%
“…In an actual industrial unit as shown in the owsheet (Wasewar et al, 2003) the thermal regeneration o gases containing water vapour and TMA can be ÿrst cooled in a falling ÿlm type of condenser where most of the TMA will be absorbed by the condensing water vapour. It is well known that when the direction of heat and mass transfer is the same (such as in this case) relatively high mass transfer coe cient are realized (Bennett and Myers, 1962).…”
Section: Thermal Regeneration and Absorption Of Tmamentioning
confidence: 99%
See 2 more Smart Citations